Diagnosis and outcome of Clostridium difficile infection by toxin enzyme immunoassay and polymerase chain reaction in an island population. Issue 2 (February 2017) - Kumar, Shankar; Pollok, Richard; Muscat, Ivan; Planche, Timothy
Abstract: Background and Aim: Clostridium difficile infection (CDI) is a potentially life‐threatening cause of diarrhea. Correct laboratory diagnosis is essential to differentiate CDI from other causes of diarrhea. A positive fecal C .  difficile toxin (CDT) is the best indicator of CDI, but the significance of a positive fecal nucleic acid amplification test (NAAT) remains unclear. Our aim was to elucidate the significance of CDI diagnostics in patients in Jersey. Methods: A retrospective, 5‐year study was conducted at an island district general hospital of patients who developed CDI. Patients were grouped according to CDT and NAAT status and their association with outcome (indicators of severity and 30‐day case‐fatality rate) compared. Results: A total of 207 specimens were toxin positive, 92 NAAT positive and toxin negative, and 39 had a stool sample negative by both toxin and NAAT testing. A positive toxin stool sample was associated with both significantly higher white cell count (14.5 × 10 9 /L vs 11.3 × 10 9 /L, P  = 0.003) and C‐reactive protein (114.7 mg/dL vs 82.9 mg/dL, P  = 0.001), but NAAT positivity was not ( P  = 0.269, 0.728). A positive CDT assay was a significant independent predictor of death (odds ratio [OR]: 1.89 [95% CI: 1.04–3.43], P  = 0.046), but a positive NAAT in CDT negative samples was not (OR: 1.02 [95% CI: 0.34–3.12], P  = 1.0). Conclusions: The findings of this study, derived from evolving clinical practice, provide greater clarity in the interpretation of CDI diagnostics. In CDT‐negative disease, a positive NAAT neither predicts disease severity nor mortality. NAAT‐positive and toxin‐negative patients require instigation of infection control measures, but the need for specific treatment remains unclear.